(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
In present studies high-performance liquid chromatography (HPLC) method for trandolapril is developed and subsequently validated. The method utilizes an Xterra MS C18 column at 35°C temperature, gradient elution with aqueous potassium dihydrogen phosphate having pH-3.0 by orthophosphoric acid and combination with acetonitrile as the mobile phase. We are reporting here simultaneously the separation of all related impurities and degradation products of trandolapril formed under different stress conditions as per ICH Q1A (R2) guideline. Trandolapril showed labile behavior in acidic, basic and oxidative stress conditions. The developed method was extensively validated and proved to be robust. The developed method has shown excellent linearity over the range from 0.10 to 3.0 μg/mL. The correlation coefficient(r) is 0.999. The % recovery value of trandolapril and their two impurities ranged from 97.98 to 100.55%, respectively.